AQUAPONIC SYSTEM CONSTRUCTION TECHNIQUES USING TARPAULIN AND PLASTIC WASTE IN THE AREA OF GAMPONG RUYUNG MESJID RAYA DISTRICT ACEH BESAR REGENCY: TEKNIK PEMBUATAN AQUAPONIK DENGAN TERPAL DAN LIMBAH PLASTIK BERLOKASI DI WILAYAH GAMPONG RUYUNG KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Kurnia; Zahrul Fuadi; Mulyanti; Dewi Yana; Mizar Liyanda; Fanny Indah Sari Berutu; Rizka Maula; Nida Khafiyya; Fuji Sintia Armi; Rachmat Hidayat; Mulla Kemalawaty; Hayatun Nufus; Tarmizi; Humeira; Nanda Fitriah; Ali Afwanuddin; Ika Rezvani Aprita; Magfirah; Endiyani; Irhami; Zulvia Maika Letis (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
This study develops an aquaponics system using tarpaulin ponds and recycled plastic waste as planting media. Conducted in Gampong Ruyung, Mesjid Raya Subdistrict, Aceh Besar, the project involved community participation through socialisation and demonstration. The pond was constructed with durable tarpaulin and bamboo frames, while plastic bottles served as planting containers. A water circulation system with PVC pipes and aerators maintained water quality, enabling optimal growth of fish and vegetables. Results show that this aquaponics model is land- and water-efficient, environmentally friendly, and supports local knowledge and economic opportunities.